(untitled) (Research, Society and Development, 2024)
The pomegranate (Punica granatum) is a fruit with a long history of medicinal use due to its numerous health benefits. Recently, science has been investigating the bioactive compounds in pomegranate, such as polyphenols, flavonoids, tannins, and anthocyanins, which are responsible for their therapeutic properties. This article aims to present a literature review that looks at information on the therapeutic functionalities of pomegranate and examines the relationship between the structure and activity of its functional components. Studies indicate that pomegranate possesses antioxidant, anti-inflammatory, antimicrobial, and anticancer properties. Polyphenols such as punicalagin and ellagic acid exhibit potent antioxidant properties, while flavonoids are shown to be effective in preventing cardiovascular diseases and cancer. Additionally, tannins and anthocyanins have significant antimicrobial effects. Understanding the detailed relationship between the structure and activity of these compounds is crucial to identify the main components responsible for pomegranate’s benefits and to develop new therapeutic approaches based on natural products. This review aims to provide a solid foundation for future research and clinical applications.